Antioxidant properties of lignin extracted from cotton stalks by ethanol solution-assisted liquid hot water before and after adding supercritical CO2. (April 2022) - Yang, Tao; Li, Zhiyi; Wei, Wei; Wang, Xiaojuan; Liu, Fengxia; Xu, Xiaofei; Liu, Zhijun
Abstract: In order to turn waste into treasure, it is very important to study the characteristics of various components in the cotton stalk. This paper studied the changes in cotton stalk lignin yield and antioxidant capacity before and after the addition of CO2 to ethanol solution. To ensure the purity of lignin, liquid hot water (LHW) was used to degrade hemicellulose and pectin. Using response surface methodology, the optimal process conditions at each stage were determined. The best conditions for LHW pretreatment were that the temperature of 210 ℃, solid/water (1/13, w/v), time 32 min, and hemicellulose residual 2.23%. The predicted optimum conditions for ethanol solution (ES) were 220 ℃, 80% of ethanol content, 1 h, and obtained 53.82% lignin in totally. The best predict conditions for the supercritical CO2 ethanol solution (SCES) were 207 ℃，pressure 11 MPa, 40% of ethanol content, 1 h, and the total lignin yield was 75.41%. And the antioxidant capacity of SCES lignin was slightly stronger than ES lignin at the same temperature. The strongest oxidation resistance temperature was 220 ℃, the radical scavenging activities (RSA) of ABTS of SCES lignin was 94.32% higher than ES lignin 2.68%, and the DPPH RSA of SCES lignin was 78.42% higher than ES lignin 1.28%. Besides in the infrared spectrum that SCES lignin lacked the 1660 cm −1 band meant that didn't occur α-carbonyl substitution reaction in the process. And other properties of lignin were similar between ES and SCES methods. Highlights: The optimal parameters of each process was determined by Response Surface method. Adding supercritical CO2, improved the yield and antioxidant capacity of lignin. No catalyst, no pollution to the environment.